Distinct Affinity of Binding Sites for S-Layer Homologous Domains in Clostridium thermocellum and Bacillus anthracis Cell Envelopes - Chauvaux, Sylvie (American Society for Microbiology, 1999)
Binding parameters were determined for the SLH (S-layer homologous) domains from the Clostridium thermocellum outer layer protein OlpB, from the C. thermocellum S-layer protein SlpA, and from the Bacillus anthracis S-layer proteins EA1 and Sap, using cell walls from C. thermocellum and B. anthracis. Each SLH domain bound to C. thermocellum and B. anthracis cell walls with a different K(D), ranging between 7.1 × 10(−7) and 1.8 × 10(−8) M. Cell wall binding sites for SLH domains displayed different binding specificities in C. thermocellum and B. anthracis. SLH-binding sites were not detected in cell walls of Bacillus subtilis. Cell walls of C. thermocellum lost their affinity for SLH domains after treatment with 48% hydrofluoric acid but not after treatment with formamide or dilute acid. A soluble component, extracted from C. thermocellum cells by sodium dodecyl sulfate treatment, bound the SLH domains from C. thermocellum but not those from B. anthracis proteins. A corresponding component was not found in B. anthracis.